Brain metastases: Nanomedicine-boosted diagnosis and treatment - Liang Han (Elsevier, 2022)
Brain metastases are intracranial recurrence of extracranial malignant tumors with a high incidence and poor prognosis. Owing to the particularity of intracranial localization, clinical diagnosis (neuroimaging and biopsy) of brain metastases is associated with shortcomings such as delayed diagnosis and biopsy invasiveness. Clinical treatment modalities consist of local therapies (resection and radiotherapy) and systemic therapies (chemotherapy, targeted therapy and immunotherapy). However, the efficiency of clinical therapies is severely hindered by 1) neurological impairment, 2) relapse, 3) blood-brain barrier, and 4) therapy resistance. Nanomedicine possesses great potentials in combating these clinical issues. This article reviewed backgrounds and recent advances of applying nanomedicine to address these above issues in clinical diagnosis and treatment of brain metastases.